joom | júm, n. (Oxford English Dictionary, 2023)
Objectives The therapeutic goals for alopecia areata (AA) are to suppress local immune inflammation, restore hair follicle structure, and improve surrounding blood perfusion. However, current efficacy evaluations largely rely on subjective clinical observation and lack objective quantitative methods. High-frequency ultrasound (HFUS) can clearly display the location and morphology of hair follicles. Combined with microvascular assessment techniques, it enables quantitative detection of low-velocity blood flow and related parameters, providing an objective basis for evaluating AA treatment efficacy. Methods Forty-five patients with AA who received intralesional therapy underwent HFUS (measuring epidermal/dermal thickness and hair follicle length/width) and ultrasound microvascular assessment, including spectral Doppler measurement of peak systolic velocity (PSV), resistance index (RI), and power Doppler measurement of vascular index (VI) before and after treatment. Patients were divided into a responder group (n = 37) and an ineffective group (n = 8) based on the reduction rate of the SALT score. The Mann-Whitney U test and Wilcoxon signed-rank test were used for comparisons between groups and within the responder group (pre-treatment versus post-treatment), respectively. Results Baseline characteristics showed no statistically significant differences (all p > .05). Patients in the ineffective group exhibited poorer hair follicle morphology (shorter length, greater width, and lower length-to-width ratio), but higher PSV and VI compared to the responder group (p < .05). In the responder group, treatment significantly improved hair follicle morphology, increased PSV and VI (p < .05), but RI showed no change. Conclusions (1) HFUS technology can observe changes in AA hair follicle structure during the diagnosis and treatment process, evaluating the effectiveness of treatment regimens in improving AA disease progression. (2) SMI combined with Doppler flow parameters can monitor changes in the perifollicular microcirculation in AA, reflecting the improvement of microcirculation during the diagnosis and treatment of AA. (3) The synergistic application of HFUS and SMI technologies can provide an objective imaging basis for the clinical evaluation of AA treatment efficacy, demonstrating promising clinical application prospects.